Oral health status of schoolchildren living in rural and urban areas in southern Brazil - Ângela DALLA NORA; Andressa DALMOLIN; Larissa D'Olanda GINDRI; Carlos Heitor Cunha MOREIRA; Luana Severo ALVES; Júlio Eduardo do Amaral ZENKNER (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study assessed the effect of area of residence (rural vs. urban) on dental caries experience among southern Brazilian schoolchildren. This cross-sectional survey was conducted in Rosário do Sul, southern Brazil, and included 373 9-14-year-old schoolchildren attending public municipal schools (122 living in the rural area, and 251, in the urban area). Data collection included a questionnaire and a clinical examination. Clinical examination of the permanent dentition involved visible plaque index, gingival bleeding index and dental caries experience (non-cavitated and cavitated, inactive and active lesions). Samples of water were collected to check the fluoride concentration. Caries prevalence and extent using different criteria were compared between rural and urban schoolchildren using the chi-square test and the Mann-Whitney test, respectively. The association between explanatory variables and the extent of caries activity (number of active caries lesions) was assessed using Poisson regression. When caries was recorded at the cavity level (WHO criterion), no difference was observed between rural and urban populations (p ≥ 0.05). Conversely, higher caries prevalence and extent were found among urban schoolchildren when active non-cavitated lesions were also computed (p < 0.05). In the adjusted Poisson regression model, urban schoolchildren were 57% more likely to present more active lesions than rural students (RR = 1.57; 95%CI = 1.29-1.92). Rural communities did not have sufficient fluoride in the water supply, whereas ideal concentrations were detected in the urban areas. In conclusion, this cross-sectional study found that urban schoolchildren showed greater caries experience than rural students, and that this increment was related to active non-cavitated lesions.